Apeiron : A Journal for Ancient Philosophy and Science (De Gruyter, 1967)
Apeiron is dedicated to the study of ancient philosophy, ancient science, and problems that concern both fields. The journal publishes high-quality research papers in these areas of ancient Greco-Roman intellectual history; it also contains papers dealing with the reception of ancient philosophical and scientific ideas in the later western tradition. The articles meet the highest standards of scholarship and philosophical insight.